Oxidative stress induces ferroptotic cell death in retinal pigment epithelial cells - Totsuka, Kiyohito; Ueta, Takashi; Uchida, Takatoshi; Roggia, Murilo F.; Nakagawa, Suguru; Vavvas, Demetrios G.; Honjo, Megumi; Aihara, Makoto (Experimental eye research, 2019)
The dysfunction and cell death of retinal pigment epithelial (RPE) cells are hallmarks of late-stage dry (atrophic) age-related macular degeneration (AMD), for which no effective therapy has yet been developed. Previous studies have indicated that iron accumulation is a source of excess free radical production in RPE, and age-dependent iron accumulation in RPE is accelerated in patients with dry AMD. Although the pathogenic role of oxidative stress in RPE in the development of dry AMD is widely accepted, the mechanisms of oxidative stress-induced RPE cell death remain elusive. Here, we show that ferroptotic cell death, a mode of regulated necrosis mediated by iron and lipid peroxidation, is implicated in oxidative stress-induced RPE cell death in vitro. In ARPE-19 cells we observed that the ferroptosis inhibitors ferrostatin-1 and deferoxamine (DFO) rescued tert-butyl hydroperoxide (tBH)-induced RPE cell death more effectively than inhibitors of apoptosis or necroptosis. tBH-induced RPE cell death was accompanied by the three characteristics of ferroptotic cell death: lipid peroxidation, glutathione depletion, and ferrous iron accumulation, which were all significantly attenuated by ferrostatin-1 and DFO. Exogenous iron overload enhanced tBH-induced RPE cell death, but this effect was also attenuated by ferrostatin-1 and DFO. Furthermore, mRNA levels of numerous genes known to regulate iron metabolism were observed to be influenced by oxidative stress. Taken together, our observations suggest that multiple modes of cell death are involved in oxidative stress-induced RPE cell death, with ferroptosis playing a particularly important role. •Oxidative stress-induced RPE cell death is rescued by ferroptosis inhibitors.•Lipid peroxidation, glutathione depletion, and Fe2+ accumulation are observed.•Iron overload enhances oxidative stress-induced RPE cells death.•Gene expressions of iron metabolism regulators are affected by oxidative stress in RPE cells.